2013
DOI: 10.1128/aem.01680-13
|View full text |Cite
|
Sign up to set email alerts
|

Differential Growth of and Nanoscale TiO 2 Accumulation in Tetrahymena thermophila by Direct Feeding versus Trophic Transfer from Pseudomonas aeruginosa

Abstract: dNanoscale titanium dioxide (TiO 2 ) is increasingly used in consumer goods and is entering waste streams, thereby exposing and potentially affecting environmental microbes. Protozoans could either take up TiO 2 directly from water and sediments or acquire TiO 2 during bactivory (ingestion of bacteria) of TiO 2 -encrusted bacteria. Here, the route of exposure of the ciliated protozoan Tetrahymena thermophila to TiO 2 was varied and the growth of, and uptake and accumulation of TiO 2 by, T. thermophila were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 49 publications
3
43
1
1
Order By: Relevance
“…276 Other indirect physical effects derive from ENMs adhering to the organism surface, 277 light shading, 278 or internal food displacement. 99 Near-field exposures (Fig. 3) can result in biological hazards from specific ENMs based on their properties (e.g., electronic).…”
Section: How Should Concepts Such As Exposure Conditions Enm Transfomentioning
confidence: 99%
“…276 Other indirect physical effects derive from ENMs adhering to the organism surface, 277 light shading, 278 or internal food displacement. 99 Near-field exposures (Fig. 3) can result in biological hazards from specific ENMs based on their properties (e.g., electronic).…”
Section: How Should Concepts Such As Exposure Conditions Enm Transfomentioning
confidence: 99%
“…For instance, NPs-microorganism heteroaggregation can lead to increased removal of NPs from wastewater during secondary treatment [106,[115][116][117][118]. Interactions between cell walls of microorganisms and NPs are also thought to precede uptake and toxicity [107,108,[110][111][112]116,119], and may be important for trophic transfer of NPs in both aquatic and terrestrial environments [108,[119][120][121].…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
“…[60][61][62][63] However, several NPs with conflicting results have been reported to have no biomagnification effects in food chains. [64][65][66][67] Tangaa et al 68 and Unrine et al 69 suggested that the discrepancies among BMFs could be due to both abiotic (eg, environmental parameters) and biotic (eg, organism physiology and life-history traits, foodweb structure, and analyses of whole-body vs single-organ concentration) that affect the efficiency of trophic transfer.…”
mentioning
confidence: 99%